2021
DOI: 10.3390/toxins13010023
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Nutrients, Temperature, and Competition of Native and Alien Cyanobacteria Species Growth and Cyanotoxin Production in Temperate Lakes

Abstract: Global warming and eutrophication contribute to formation of HABs and distribution of alien cyanobacteria northward. The current study assessed how alien to Europe Sphaerospermopsis aphanizomenoides and Chrysosporum bergii will co-occur with dominant native Planktothrix agardhii and Aphanizomenon gracile species under changing conditions in temperate freshwaters. The experiments were carried out to examine the effect of nutrients and temperature on the growth rate of cyanobacteria, production of cyanotoxins, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…It is known that several species of Vibrio are pathogenic and may cause toxigenic cholera and vibriosis [67]. In natural water bodies, rising water temperature [68], which is one of the major causes of cyanobacterial blooms and proliferation [69,70], may also provide an optimal environment for the occurrence of Vibrio species [66,71]. Moreover, the dissolved organic matter resulting from intensive phytoplankton blooms, especially cyanobacteria-derived organic matter, can significantly support the growth of potentially pathogenic Vibrio species [71][72][73].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that several species of Vibrio are pathogenic and may cause toxigenic cholera and vibriosis [67]. In natural water bodies, rising water temperature [68], which is one of the major causes of cyanobacterial blooms and proliferation [69,70], may also provide an optimal environment for the occurrence of Vibrio species [66,71]. Moreover, the dissolved organic matter resulting from intensive phytoplankton blooms, especially cyanobacteria-derived organic matter, can significantly support the growth of potentially pathogenic Vibrio species [71][72][73].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the number of publications increased rapidly each year, at an average annual rate of 12.4%, and 252 related publications were published in 2020 (Figure 1). Global warming has severely affected shallow reservoirs, releasing pollutants from sediments and accelerating eutrophication [41,42]. Researchers have found that temperature effects largely determine the distribution of different cyanotoxins in Europe [43].…”
Section: Variation In and Distribution Of The Total Publication Numbermentioning
confidence: 99%
“…To date, most research has focused on the evaluation of environmental conditions that trigger toxin production and its dynamics, which can be essential for understanding of the toxicity and its predicting [ 31 ]. Although the role of environmental factors is not sufficiently understood and the results were widely disputed, many physiological studies demonstrated the influence of light, nutrient availability, temperature, pH and dissolved inorganic carbon (DIC) on enhancing or suppressing the production of different toxic compounds [ 88 , 96 , 97 , 111 , 118 , 119 , 120 , 121 ]. Evidence suggested that generally increased temperatures and light favor the growth of toxin producers and can enhance the toxin production [ 83 , 88 , 122 ], but at times, as for other factors, conflict results.…”
Section: Phycotoxins and Factors That Affect Their Productionmentioning
confidence: 99%